Penempatan Tanaman Upakara sebagi Elemen Lunak Taman Pekarangan Rumah Ditinjau dari Aspek Filosofi Budaya Bali di Kecamatan Payangan, Kabupaten Gianyar, Provinsi Bali - AMBARANI, DESAK PUTU LOLA; SUDARSANA, A.A. GEDE DALEM; SARWADANA, SANG MADE (Jurnal Arsitektur Lansekap, 2017)
The Placement of Ritual Plants as Soft Elements of Garden Reviewed from Aspect of Balinese Culture Philosophy in District of Payangan, Gianyar Regency, Province of Bali Hindus community in Bali always held a religious rituals throughout the year. Most of the ritual elements are descended from plants which are well known as “ritual plants”. Traditional garden of Bali should use ritual plants as a landscaping plant. Objectives of this research were to determine ritual plant as a soft elements of garden located in district of Payangan, Gianyar regency, province of Bali and to review the placement ritual plants from aspects of Balinese philosophy. Data were collected from three villages in Payangan throught field survey. Results showed that there were as many as 48 samples of house were surveyed with 80 species of ritual plants found as it used as elements of garden in district of Payangan. The placement of ritual plants were appropriate to the philosophy concepts of Balinese culture which were Tri Mandala and Asta Dala. Unfortunately, these concept were not implemented by the people in Payangan district because of the lack of knowledge.